Gay Peoples Union Records, 1971-1984: Text Corpus of AV Materials - (:unkn) unknown (My University, 2021)
The Gay Peoples Union (GPU), was the first gay rights organization in Milwaukee, Wisconsin and one of the earliest such groups in the state. This text corpus was derived from audio recordings of Gay Perspective, a radio program produced by GPU and broadcast on local radio stations from 1971 to 1972, and other public presentations given by GPU members as part the organization's educational mission. The full finding aid for the Gay People's Union (GPU) Collection can be found here: http://digital.library.wisc.edu/1711.dl/wiarchives.uw-mil-uwmmss0240